Pasantías en planta fabricadora de hormigón (2022)
The present work has several purposes, one of them is to show part of the history of the company Polimix Colombia, its economic activity, portfolio among other relevant data. Similarly, documenting the work of production of ready-mix concrete during professional practices, where the quality control of concrete in plant and on site was analyzed by means of taking settlements and making cylinders, in the same way and with the support of the quality area , the cement water relationship was monitored, observing how the resistance at mature age (28 days) would be affected if the standardized conditions were modified and the quality of the raw materials used for the same purpose was verified, a process that was carried out with the taking of laboratory tests, such as absorptions, humidity and density.